Solvent Extraction and Stripping of Pd(II) Cyanide in Cetyltrimethylammonium Bromide System - Chen, Lei; Huang*, Zhangjie; Chen, Jing (Asian Journal of Chemistry, 2013)
The solvent extraction of Pd(II) from alkaline cyanide solution by using cetyltrimethylammonium bromide as extractant has been investigated. Palladium(II) was extracted quantitatively with cetyltrimethylammonium bromide in benzene. Ammonium thiocyanate solution could be used as stripping agent. Extraction parameters of Pd(II), including cetyltrimethylammonium bromide concentration, contact time of aqueous and organic phases, organic/aqueous (O/A) phase ratio and NH4SCN concentration of aqueous phase, were studied. Almost all of the Pd(CN)42-(> 99 %) was transferred from the aqueous phase into the organic phase. Most of the Pd(II) in the organic phase can be stripped with ammonium thiocyanate aqueous solutions. The possible mechanisms of extraction and stripping were discussed.